Germline variation of TNFAIP3 in primary Sjögren's syndrome-associated lymphoma. Issue 4 (2nd September 2015) - Nocturne, Gaetane; Tarn, Jessica; Boudaoud, Saida; Locke, James; Miceli-Richard, Corinne; Hachulla, Eric; Dubost, Jean-Jacques; Bowman, Simon; Gottenberg, Jacques-Eric; Criswell, Lindsey A; Lessard, Christopher J; Sivils, Kathy L; et al.
Abstract : Background and objective: A germline and coding polymorphism (rs2230926) of TNFAIP3 (A20), a central gatekeeper of nuclear factor-kappa B (NF-kB) activation, was recently found associated with primary Sjögren's syndrome (pSS)-associated lymphoma in a French cohort. We aimed to replicate this association. Patients and methods: The rs2230926 polymorphism was genotyped in cases and controls of European ancestry from two independent cohorts from UK and France. Case control association tests were performed (Fisher's test) in the two cohorts, followed by a meta-analysis of the two cohorts. Results: The UK cohort included 308 controls and 590 patients with pSS including 31 with a history of lymphoma. The French cohort consisted of 448 controls and 589 patients with pSS including 47 with lymphoma. In both cohorts, the rs2230926 missense polymorphism was not associated with pSS. However, in the UK cohort, the rs2230926G variant was significantly associated with pSS-associated lymphoma (OR=2.74, 95% CI (1.07 to 7.03), p=0.0423, compared with patients with pSS without lymphoma, and OR=3.12, 95% CI (1.16 to 8.41), p=0.0314, compared with healthy controls) as observed in the French cohort. The meta-analysis of the two cohorts confirmed these results (OR=2.48, 95% CI (1.87 to 3.28) p=0.0037 and OR=2.60, 95% CI (1.91 to 3.53) p=0.0031, respectively). Conclusions: This study confirms the role of A20 impairment in pSS-associated lymphoma. Subtle germline abnormalities of genes leading to impaired control of NF-kB activation in B cells continuously stimulated by autoimmunity enhance the risk of lymphoma.